2018
DOI: 10.1186/s13052-018-0479-8
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D levels and parathyroid hormone variations of children living in a subtropical climate: a data mining study

Abstract: BackgroundVitamin D and intact parathyroid hormone (iPTH) play a crucial role in calcium homeostasis and bone health of children. Serum level of 25-hydroxyvitamin D (25-OHD) is considered to be the most accurate marker for vitamin D status. However, there have only been a few studies, with limited number of subjects, investigating the relationship between 25-OHD and parathyroid hormone (PTH) in children. The aim of this study was to evaluate the seasonal 25-OHD levels and its associations with intact parathyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
0
16

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 35 publications
5
25
0
16
Order By: Relevance
“…As the main source of Vitamin D is skin synthesis under direct sunlight, seasons may cause significant changes in serum levels of 25 (OH) D [14]. Between February and May, the level is lower than other times of the year according to the data mining study of Şahin et al [1]. In this study, the period of serum vitamin D level assessment had no significance, but season of birth proved important.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…As the main source of Vitamin D is skin synthesis under direct sunlight, seasons may cause significant changes in serum levels of 25 (OH) D [14]. Between February and May, the level is lower than other times of the year according to the data mining study of Şahin et al [1]. In this study, the period of serum vitamin D level assessment had no significance, but season of birth proved important.…”
Section: Discussionmentioning
confidence: 64%
“…Many studies find that gender is key factor with increasing age, i.e. the increased deficiency rate among adolescent girls' [1,21].…”
Section: Discussionmentioning
confidence: 99%
“…Güneş ışığı etkinliğinin azaldığı mevsimlerde, ilerleyen yaşlarda ve kız çocuklarında eksiklik oranı daha fazladır. D vitamini eksikliği Kuzey Yarımküre'de ılıman iklim kuşağında yer alan ilimiz ve ülkemiz için önemli bir halk sağlığı sorunudur [5,17]. İstanbul'da yapılan ve yeterlilik eşik değerinin 30 ng/ml alındığı çalışmada erken çocuklukta %40-45 civarında olan D vitamini eksikliği 10 yaşından itibaren %80-90'lara çıkmaktadır [5].…”
Section: Discussionunclassified
“…In this regard, to define optimal levels of 25(OH)D at which PTH plateaus or rapidly raises, some studies found no optimal threshold value [6, 30], whereas others report a wide range of cut points, 14 to 43 ng/mL [6, 8, 9, 29, 3139] (Fig 3). This variation in inflection points may be explained by mathematical methods used as well as other factors such as age, sex, race or ethnicity, calcium and phosphorus intake, weight status, extent of vitamin D insufficiency, pubertal status, or even inaccuracy of 25(OH)D assays [6, 40].…”
Section: Discussionmentioning
confidence: 99%